[32] Perceptions of robot-assisted surgery: Results of a survey of surgeons in Kuwait - Saad Aldousari (Taylor & Francis Group, 2018)
Objective: To gain insight into local surgeons’ perceptions of robot-assisted surgery (RAS), as the use of RAS has rapidly increased amongst hospitals worldwide and the da Vinci® Si surgical system (Intuitive Surgical Inc., Sunnyvale, CA, USA) was installed at Sabah Al-Ahmad Urology Center (SAUC) in February 2014 and at Kuwait’s Chest Disease Hospital in October 2017, with >200 robotic surgical procedures performed by robotic surgeons using these two systems, overall surgeons perceptions and acceptance of this new technology in Kuwait are largely unknown. Methods: We conducted a questionnaire-based survey distributed amongst surgeons of different subspecialties. The questionnaire had 28 questions related to the surgeon’s knowledge of RAS, it’s availability in Kuwait, and surgeons attitudes and concerns towards it. Results: There were 292 surveys, with 278 used for analysis (95.2% response rate). General surgeons, urologists, and gynaecologists constituted 54%, 23%, and 13%, respectively. The mean age of respondents was 36 years. There was a significant association between younger age groups and comfort using the technology (P< 0.05). In all, 250 surgeons (91%) had previously heard of RAS, and the majority (73%) agreed with its introduction into surgical practice mostly gynaecologists, urologists and general surgeons (P< 0.001) due to their belief of its enhanced precision and better visualisation. However, 50% of surgeons thought that laparoscopic surgery performs what RAS does. When surgeons were asked to rate factors according to their importance when choosing RAS they indicated faster recovery, lower complications, and patient demand were most important (P< 0.001) Conclusion: RAS seems to be an accepted modality amongst surgeons in Kuwait. However, surgeons remain concerned regarding the learning curve, device cost, and availability for use.